Hum. Behav. Brain 2020
DOI: 10.37716/hbab.2020010601
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of fMRI activation patterns in visual object priming

Abstract: Prior information shapes how the brain processes sensory inputs (e.g., priming effects). Recent studies of "behavioral oscillation” have demonstrated that the effects of visual object primes are temporally coordinated in the theta band to guide perception efficiently. However, the neural mechanism underlying this dynamic processing remains unclear. Here, we combine functional magnetic resonance imaging (fMRI) and a time-resolved paradigm to access high-temporal-resolution profiles of brain activation fluctuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
2
3
2
Order By: Relevance
“…However, the response was not modulated by the visuo-motor delay (Figures S2E and S2H) at any time of the hemodynamic response (Figures S2F and S2I), contrary to reported evidence when reaction times are also measured. 21 The absence of M1 BOLD modulations with visual delay is consistent with the fact that motor cortex does not activate in response to visual stimuli. However, synchronous oscillatory activity may be present in M1 and shared with V1.…”
Section: Bold Correlations In the Sensory-motor Networksupporting
confidence: 62%
See 1 more Smart Citation
“…However, the response was not modulated by the visuo-motor delay (Figures S2E and S2H) at any time of the hemodynamic response (Figures S2F and S2I), contrary to reported evidence when reaction times are also measured. 21 The absence of M1 BOLD modulations with visual delay is consistent with the fact that motor cortex does not activate in response to visual stimuli. However, synchronous oscillatory activity may be present in M1 and shared with V1.…”
Section: Bold Correlations In the Sensory-motor Networksupporting
confidence: 62%
“…However, the response was not modulated by the visuo-motor delay ( Figures S2 E and S2H) at any time of the hemodynamic response ( Figures S2 F and S2I), contrary to reported evidence when reaction times are also measured. 21 …”
Section: Resultsmentioning
confidence: 99%
“…The haemodynamic responses of M1 and S1 to vision and action events are different from those in V1 (compare panel A to panels D&G in Figure S2): the response occurred earlier (reflecting activity during action preparation 20 ), and had a more pronounced negative lobe. However, the response was not modulated by the visuo-motor delay (Figure S2, panels E&H), at any time of the haemodynamic response (Figure S2, panels F&I), contrary to reported evidence when reaction times are also measured 21 .…”
Section: Bold Correlations In the Sensory-motor Networkcontrasting
confidence: 90%
“…This is to be expected, given that M1 and S1 do not respond to visual stimuli, so a visual stimulus will not be an adequate probe of cortical excitability. Interestingly, using a similar time-resolved fMRI approach, and measuring reaction-times, Guo et al 62 observed rhythmic modulations of M1, consistently with previous report 63 . We interpret their oscillation in M1 to be related to the programming of speeded responses, whose latency oscillates with a theta rhythm 20,56,62 , like behavioural sensitivity.…”
Section: Discussionsupporting
confidence: 78%
“…What is the origin of the observed fluctuation in rapid detection performance as a function of ISI? A possible mechanism is suggested by a recent investigation of the neural substrates of behavioural oscillations in the priming effect (Guo et al, 2020). The authors in that study presented pairs of congruent or incongruent primes and probes (faces/houses) separated by densely sampled ISIs during fMRI recording.…”
Section: Discussionmentioning
confidence: 99%